Math, asked by YaminiSahib, 1 year ago

if x2+kx+6=(x+2(x+3) for all x,find the value of x

Answers

Answered by gayathri7
4
2x + kx + 6 =( (x+2)(x+3) )
kx + 2x +6 =(2x + x + 6)
kx + 2x + 6 = ( 3x+6)
kx + 2x + 6 = 3x + 6

YaminiSahib: uh actually it is x to the power 2
YaminiSahib: can you please edit the answer and tell me
gayathri7: ok
gayathri7: x2+ kx + 6 = (x+2)(x+3)
gayathri7: x2+kx + 6 = (2x+6+x)
gayathri7: x2 + kx +6 = (3x+6)
gayathri7: x2 + kx + 6 = 3x+6
YaminiSahib: thanks
Similar questions